PEMATUHAN MAKSIM KUANTITAS GRICE PADA TUTURAN GURU DALAM INTERAKSI KELAS BAHASA ARAB DI MA AL MUNAWAROH JOMBANG - Qomariyah, Lailatul; Ahya, Ahmad Sauqi (STIQ Amuntai, 2021)
The teacher's speech dominates in interactive activities with students in learning Arabic. To realize communicative and interactive learning, the teacher obeys the maxim of quantity proposed by Grice, which is to speak as briefly and clearly as possible so that the information conveyed can be understood easily. This article examines how to comply with Grice's maxim of quantity in the teacher's speech in Arabic class interaction. This research uses a qualitative case study approach in which data is collected through the documentation method and then analyzed using an interactive method. The results of this study are, the observance of the maxim of quantity in the teacher's speech is used in several categories; namely, 1) Requestives